Effect of borax on early hydration and rheological properties of reactivated cementitious material. Issue 5 (17th August 2018) - Zhang, Linglei; Ji, Yongsheng; Huang, Guodong; Gao, Furong; Dong, Zuochao
Abstract : The influence of borax on the early hydration and rheological properties of dehydrated cement paste (DCP) composite reactivated cementitious materials (DCRCM) is investigated through analysis of the hydration kinetics and measurement of rheological parameters. Results show that the presence of borax can effectively restrain the early hydration rate of DCRCM, and this leads to reductions in both the hydration products and the flocculent structure in the paste. Obvious shear thinning occurs in the fresh DCRCM paste with the increase of shear rate, followed by gradually stabilised viscosity. As the amount of borax is increased, the yield stress and plastic viscosity of DCRCM paste decrease and the rheological properties are significantly improved. However, when the amount of borax is 4%, the rheological type of DCRCM paste changes to shear thickening at a high shear rate, which is unfavourable in terms of the improvement of rheological properties.